Ecologia de Caracara plancus: implicações para o manejo populacional e redução de ocorrências no Aeroporto de Uberlândia-MG - Teixeira, Camila de Paula (2021)
This research aimed to verify if the relative density and occurrence of Caracara plancus is constant throughout the year and if it is greater at UberlândiaMG Airport than in other areas of the city. It was also intended to analyze their diet and, consequently, the available resources that interfere with their density in the studied places. It is organized in two sections entitled: 1) Temporal variation in different areas of UberlândiaMG and 2) Diet of Caracara plancus in different areas. The first section aimed to analyze the occurrences at Uberlândia Airport and whether the population density of carcarás at the Airport and other areas are similar. In addition, it was intended to observe its frequency of occurrence and whether the relative density is constant throughout the year and whether it is conditioned to abiotic and biotic factors (temperature, rain, wind intensity, relative humidity, noise levels, presence of attractions and height of ground cover). The second section aimed to analyze the diet in the municipality of Uberlândia Airport and at other locations, considering the frequency of occurrence of the items consumed, through direct observations and analysis of crop and stomach content, and whether the diet of individuals at the Airport differs from individuals from other locations.